Proton Radiation Influence on SOI FinFET Trade-Off between Transistor Efficiency and Unit Gain Frequency - Caparroz, Luis F. V.; Martino, Joao A.; Simoen, Eddy; Claeys, Cor; Agopian, Paula G. D. [UNESP]; IEEE (Ieee, 2016)
This paper studies the proton radiation influence on SOI FinFET analog parameters based on the device inversion coefficient (IC). The analysis focuses on some figures of merit in analog design like the transistor efficiency, the unity gain frequency and the intrinsic voltage gain. Although the proton radiation affects the device performance, it is possible to define an optimal analog condition by basing the analysis on the inversion coefficient, even considering the radiation impact. N-channel devices are affected in a different manner when compared to p-channel counterparts, which can be decisive depending on the application.
Keywords: FinFET; inversion coefficient; radiation; analog parameters